Pendidikan Kewirausahaan: Proyek Bisnis Meningkatkan HOTS Siswa Sekolah Vokasi - Cahyo, Mhd. Septiyan Dwi Cahyo; Gani Haryana; Brilliant Asmit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effectiveness of Project-Based Learning (PjBL) in improving students’ Higher Order Thinking Skills (HOTS) at SMK Perbankan Riau. The study was motivated by the low level of students’ higher-order thinking skills, as indicated by their limited ability to analyze, evaluate, and create solutions to contextual problems. The purpose of this research was to determine whether the implementation of PjBL could significantly improve students’ HOTS compared to conventional learning methods. This study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. Data were collected through HOTS-based pre-tests and post-tests, as well as classroom observations. The data were analyzed using normality tests, homogeneity tests, N-Gain analysis, and independent sample t-tests. The findings revealed that students who participated in Project-Based Learning demonstrated higher improvement in Higher Order Thinking Skills than those who learned through conventional methods. Furthermore, the results indicated a significant difference between the experimental and control groups. Therefore, Project-Based Learning was found to be effective in enhancing students’ Higher Order Thinking Skills. This study contributes empirical evidence regarding the implementation of Project-Based Learning in vocational education, particularly in developing Higher Order Thinking Skills among vocational high school students.